Charismatic Leadership of Caregivers in Shaping the Character of Santri at the Female Boarding School Assa’adah - Qomalasari, Nor; Farhan, Moh (UAS PRESS, 2025)
This study aims to determine the characteristics of the caregiver's charismatic leadership and the implementation of the caregiver's charismatic leadership in shaping the character of santri at Pesantren Putri Assa'adah Terboyo Semarang. This research includes field research with descriptive qualitative methods. Data were collected using interviews, observation, and documentation techniques. Data analysis was conducted through three stages, namely data reduction, data presentation, and conclusion drawing/verification. The data validity test used triangulation of techniques, time, and sources. The results of this study indicate that the charismatic leadership of the caregiver of Pesantren Putri Assa'adah Terboyo Semarang City plays a central role in shaping the character of santri through three main aspects, namely visioning, mobilizing, and enabling. In the process of character building, the Islamic boarding school applies a classical book-based teaching approach, skills training through khitobah and sorogan ngaji, consistent worship habituation, as well as education-based coaching and giving responsibility. With this holistic approach, the charismatic leadership of the caregiver is able to create a pesantren environment that is conducive to the spiritual, intellectual, and moral growth of santri in a balanced and sustainable manner.